Microwave-Assisted Cascade Cycloaddition for C–N Bond Formation: An Approach to the Construction of 1,4,5,6-Tetrahydropyrimidine and 2-Imidazoline Derivatives - An, Shujuan; Yin, Bing; Liu, Ping; Li, Xiangnan; Li, Chen; Li, Jianli; Shi, Zhen (Synthesis, 2013)
An efficient strategy for the synthesis of various 1,4,5,6-tetrahydropyrimidine and 2-imidazoline derivatives has been reported. The reactions proceeded from nitriles with ethylenediamine or 1,3-diaminopropane via cascade cycloaddition in the presence of CuL2 (L = 2-hydroxy-2-phenylacetate) to afford the corresponding 1,4,5,6-tetrahydropyrimidine or 2-imidazoline derivatives under reflux conditions or microwave irradiation in excellent yields.
Keywords: catalysis; cycloaddition; nitrogen heterocycles; nitriles; synthesis